Pelatihan Pengelolaan Perpustakaan Berbasis Teknologi Informasi bagi Petugas Perpustakaan SD Negeri Menuju Pembentukan Karakter Gemar Baca Pebelajar di Kota Malang - Purwati, Titik; Ahmad, Harun (Jurnal ABM Mengabdi, 2017)
Research results, in some primary school (elementary school) in Malang found conditions in the handling of corporate governance of the library is still not running properly. Because the officers library in SD in Malang/it isnot education background-capable of managing libraries, on average they still haven't been training the management library especially technology-based information. The way out is a need to provide training as needed. So training can meet his needs, then conducted the activities of pre test and post test training to participants and the now responsi given to the principal officer and library. Outline of training methods based on need by way of grant of lectures, assignments and practice directly. The results of the training activities, understanding of the theory and management of the library be increased. Mastery of the officer in managing books become proficient, school party responsi very nice and understanding of program implementation application management library. The officers have felt their effectiveness in dealing with library services.